Creating sustainable cities - Girardet, Herbert (Totnes Green Books, 1999)
How can we put the pulsing heart of conviviality back into our cities? How can we make sure of creating cities of diversity for the new millennium?places of cultural vigour and physical beauty that are also sustainable in economic and environmental terms? This Schumacher Briefing shows the way forward.
Includes bibliographical references (p. 76-77).
Keywords: Urban ecology (Sociology)